Emerging roles for microtubules in angiosperm pollen tube growth highlight new research cues - Onelli, Elisabetta; Idilli, Aurora I.; Moscatelli, Alessandra (Frontiers in Plant Science, 2015)
In plants, actin filaments have an important role in organelle movement and cytoplasmic streaming. Otherwise microtubules have a role in restricting organelles to specific areas of the cell and in maintaining organelle morphology. In somatic plant cells, microtubules also participate in cell division and morphogenesis, allowing cells to take their definitive shape in order to perform specific functions. In the latter case, microtubules influence assembly of the cell wall, controlling the delivery of enzymes involved in cellulose synthesis and of wall modulation material to the proper sites. In angiosperm pollen tubes, organelle movement is generally attributed to the acto-myosin system, the main role of which is in distributing organelles in the cytoplasm and in carrying secretory vesicles to the apex for polarized growth. Recent data on membrane trafficking suggests a role of microtubules in fine delivery and repositioning of vesicles to sustain pollen tube growth. This review examines the role of microtubules in secretion and endocytosis, highlighting new research cues regarding cell wall construction and pollen tube-pistil crosstalk, that help unravel the role of microtubules in polarized growth.